2015
DOI: 10.3126/ijasbt.v3i1.11896
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability for Agro-Morphological Important Traits in Aman Rice (Oryza Sativa L.)

Abstract: The present study was conducted in the experimental farm, Sher-e-Bangla Agricultural University (SAU), Dhaka during July 2013-December2013. The analysis of variance revealed significant deviation for all the characters studied and indicated the existence of variation among thegenotypes. The PCV values were slightly higher than the respective GCV values for all the characters except unfilled grains per panicleindicating that the characters were less influenced by the environment. Total tillers per plant, effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
4
8
0
Order By: Relevance
“…It also indicates narrow genetic base for these traits and improvement in these traits could be brought about by hybridization or induced mutation to widen the genetic base followed by pedigree selection in advance generation (Gangashetty et al, 2013). Ganapati et al (2014) and Sarwar et al (2015). However, in majority of the cases, these estimates were found to be low for days to 50 % flowering and fertility percentage; moderate to low for plant height and panicle length; moderate to high for panicle number,100-grain weight and plot yield and high for number of fertile grains per panicle, harvest index and grain yield per plant.…”
Section: Resultsmentioning
confidence: 99%
“…It also indicates narrow genetic base for these traits and improvement in these traits could be brought about by hybridization or induced mutation to widen the genetic base followed by pedigree selection in advance generation (Gangashetty et al, 2013). Ganapati et al (2014) and Sarwar et al (2015). However, in majority of the cases, these estimates were found to be low for days to 50 % flowering and fertility percentage; moderate to low for plant height and panicle length; moderate to high for panicle number,100-grain weight and plot yield and high for number of fertile grains per panicle, harvest index and grain yield per plant.…”
Section: Resultsmentioning
confidence: 99%
“…The use of molecular markers for assessing genetic diversity has received a great deal of attention in recent years (Woldesenbet et al, 2015). Bharathi et al (2014) and Sarwar et al (2015) stated that the study of genetic diversity in crops is essential for high productivity and crop improvement. Traditional sesame landraces as well as related wild species are important source of genetic diversity for breeders and therefore form the backbone of agricultural production (Odongo et al 2015;Sharma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Days to 50% flowering, plant height, panicle length, specific leaf weight and specific leaf area exhibited high heritability value and moderate to low genetic gain suggested that the inheritance of such traits might be under the control of both additive and non-additive gene effects. Therefore, selection of genotypes on the basis of phenotypic performance of the above traits may not be effective (Dhanwani et [6,9,21,12,19,24] .…”
Section: Resultsmentioning
confidence: 99%